2019
DOI: 10.32598/ajnpp.5.2.73
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Personality Traits and Marital Satisfaction With Mediating Positive and Negative Affects

Abstract: Background: Various protective mechanisms have been proposed to explain how positive and negative emotions increase marital satisfaction.Objectives: This study aimed to determine the relationship between personality traits and marital satisfaction with the mediating role of positive and negative affects. Materials and Methods:The research method was descriptive and correlational. In this research, 300 married women living in the eastern part of Tehran City, Iran, were selected by the available sampling method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In another study, Renna et al [10] showed that the compassion-based intervention reduced the feelings of loneliness and increased emotional regulation in individuals with high levels of chronic distress. Marital satisfaction is another factor that may be related to attitudes toward marital infidelity in couples, and it is defined as the extent to which the couples are happy with the fulfillment of their needs by their partners [11]. Moreover, marital satisfaction is a situation in which husband and wife often feel happy and satisfied with marriage and with each other.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Renna et al [10] showed that the compassion-based intervention reduced the feelings of loneliness and increased emotional regulation in individuals with high levels of chronic distress. Marital satisfaction is another factor that may be related to attitudes toward marital infidelity in couples, and it is defined as the extent to which the couples are happy with the fulfillment of their needs by their partners [11]. Moreover, marital satisfaction is a situation in which husband and wife often feel happy and satisfied with marriage and with each other.…”
Section: Introductionmentioning
confidence: 99%